2007
DOI: 10.1074/jbc.m606295200
|View full text |Cite
|
Sign up to set email alerts
|

Channeling of Eukaryotic Diacylglycerol into the Biosynthesis of Plastidial Phosphatidylglycerol

Abstract: Plastidial glycolipids contain diacylglycerol (DAG) moieties, which are either synthesized in the plastids (prokaryotic lipids) or originate in the extraplastidial compartment (eukaryotic lipids) necessitating their transfer into plastids. In contrast, the only phospholipid in plastids, phosphatidylglycerol (PG), contains exclusively prokaryotic DAG backbones. PG contributes in several ways to the functions of chloroplasts, but it is not known to what extent its prokaryotic nature is required to fulfill these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 88 publications
4
30
0
Order By: Relevance
“…It is undetectable in the isolated envelope fraction by conventional techniques. The PA level in the envelope is possibly close to PA levels in thylakoids, which was reported to be 0.08 mol% mainly prokaryotic PA (27). MGD1 was activated by several molecular species of PA from either a prokaryotic or eukaryotic nature.…”
Section: Discussionmentioning
confidence: 92%
“…It is undetectable in the isolated envelope fraction by conventional techniques. The PA level in the envelope is possibly close to PA levels in thylakoids, which was reported to be 0.08 mol% mainly prokaryotic PA (27). MGD1 was activated by several molecular species of PA from either a prokaryotic or eukaryotic nature.…”
Section: Discussionmentioning
confidence: 92%
“…This differs from the situation in Arabidopsis, where levels of all phospholipids show a positive correlation and all glycoglycerolipids show a negative correlation with Pi supply (Dörmann and Benning, 2002). By contrast, 36:x SQDG species, which are synthesized from the ER-derived secondary DAG pool in the chloroplast (Fritz et al, 2007;Li-Beisson et al, 2010;Boudière et al, 2014), clustered in group II (b) and showed the typically documented decrease with increasing Pi supply in H. prostrata. These contrasting responses resulted in an overall sulfolipid profile that responded very little to altered Pi availability.…”
Section: Chloroplast Lipid Metabolism Is Perturbed At Higher Leaf Pi mentioning
confidence: 49%
“…In Arabidopsis leaves, 34:x lipid species show mixed acyl chain configurations suggesting biosynthesis from both ER-derived and chloroplast DAG pools, making it hard to determine their precise origin. In Arabidopsis leaves, PG 34:4, SQDG 34:3/34:4, MGDG 34:4 to 34:6, and DGDG 34:1 species almost exclusively carried the C-16 fatty acid in the sn-2 position (DGDG 34:4 species were not detected; Devaiah et al, 2006;Maatta et al, 2012), which would suggest that these lipid species are synthesized from the primary DAG pool in the chloroplast inner envelope membrane via the so-called prokaryotic pathway (Fritz et al, 2007;Li-Beisson et al, 2010;Boudière et al, 2014). In Arabidopsis, both PG and sulfolipids are essential for chloroplast structure and function, but only about 30% of PG species are actually produced in the chloroplast Yu and Benning, 2003).…”
Section: Chloroplast Lipid Metabolism Is Perturbed At Higher Leaf Pi mentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma membrane is enriched in PA (3e4 mol % of lipids [11]) whereas, in the chloroplast membranes, PA is very low, never detected in the chloroplast envelope, and around 0.1 mol % of lipids in tobacco thylakoids as reported by [12]. The authors detected mainly a form of PA with C18:1 at sn-1 and C16:0 at sn-2 position of glycerol, which is considered as a prokaryotic form of glycerolipid typically synthesized in chloroplasts as we will see below.…”
Section: Levels Of Phosphatidic Acid In Plant Cellsmentioning
confidence: 68%